Technology Adoption Subsidies: An Experiment with Managers - Rob Aalbers; Eline van der Heijden; Jan Potters; Daan van Soest; Herman Vollebergh (Tinbergen Institute, 2007)
We evaluate the impact of technology adoption subsidies on in- vestment behavior in an individual choice experiment. In a laboratory setting professional managers are confronted with an intertemporal decision problem in which they have to decide whether or not to search for, and possibly adopt, a new technology. Technologies differ in the per-period benefits they yield, and their purchase price increases with the per-period benefits provided. We introduce a subsidy on the more expensive technologies (that also yield the larger per-period benefits), and find that the subsidy scheme induces agents to search for and adopt these more expensive technologies even though the subsidy itself is too small to render these technologies profitable. We speculate that the result is driven by the positive connotation (affect) that the concept 'subsidy' invokes.
Keywords: C9; D8; H2; 330; framed field experiment; search model; technology subsidies; Technologiewahl; Ökonomischer Anreiz; Test; Suchtheorie; Theorie